Unusual cutaneous signs associated with an Epstein Barr virus infection. - Cadilhac, H.; Boulinguez, S.; Icart, J.; Bonafé, J.L. (European Journal of Pediatric Dermatology, 2018)
We reported a case of a nineteen-month-old child with unusual cutaneous signs (desquamation of the fingertips with edema and erythema). These cutaneous manifestations could be linked to an Epstein Barr virus infection, because they were associated with pharyngitis, lymphadenopathy, hepatic cytolysis, serologic Epstein Barr virus profile and Epstein Barr virus isolation from nasopharyngeal swabs. No other etiology could be shown.